Geochemical and Environmental Assessment of Heavy Metals in the Gulf of Guayaquil 2019-2021 (LACCEI, 2024)
This study seeks to contribute to the knowledge of the current situation of heavy metal pollution in the Gulf of Guayaquil (GG), an area where multiple productive sectors are developed and where most of the country's mangroves are located. The objective of this research is to evaluate the geochemical behavior of heavy metals in the gulf by estimating the degree and distribution of pollution in the period 2019-2021. Data were obtained from monthly sediment chemical reports provided by the company CGU S.A. Concentrations of As, Cd, Cu, Pb and Zn located at 7 points in the GG were analyzed. The accumulation zones and the degree of pollution were determined by indexing methods. The data were correlated and a cluster analysis was performed to determine possible sources. Accumulation and pollution of Cu and Cr were found in 3 estuaries in the city of Guayaquil. In 2020 there was a higher degree of pollution than in the other periods. The areas with the highest accumulation showed a higher load of sediment pollution. The level of ecological risk in all periods remained low. The possible sources of contamination are associated with anthropogenic activity from the different productive sectors around the gulf.